2011
DOI: 10.4992/jjpsy.82.41
|View full text |Cite
|
Sign up to set email alerts
|

Using the Implicit Association Test (IAT) to measure implicit shyness

Abstract: Previous research has shown that implicitly measured shyness predicted spontaneous shy behavior in social situations, while explicit self-ratings of shyness predicted controlled shy behavior (Asendorpf, Banse, & Mücke, 2002). The present study examined whether these same results would be replicated in Japan. In Study 1, college students (N=47) completed a shyness Implicit Association Test (IAT for shyness) and explicit self-ratings of shyness. In Study 2, friends (N=69) of the Study 1 participants rated those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The correlation between explicit shyness on the self‐report scale and implicit shyness on the conventional IAT was weak, consistent with previous findings ( r = .12 in Aikawa & Fujii, ; r = .23 in Fujii, Sawaumi, & Aikawa, ). This is also true for the correlation between explicit shyness and implicit shyness on the self‐targeted ST‐IAT ( r = −.04 in Fujii, Sawaumi, & Aikawa, ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The correlation between explicit shyness on the self‐report scale and implicit shyness on the conventional IAT was weak, consistent with previous findings ( r = .12 in Aikawa & Fujii, ; r = .23 in Fujii, Sawaumi, & Aikawa, ). This is also true for the correlation between explicit shyness and implicit shyness on the self‐targeted ST‐IAT ( r = −.04 in Fujii, Sawaumi, & Aikawa, ).…”
Section: Discussionsupporting
confidence: 90%
“…We adopted a Japanese version of the Shyness IAT developed and validated in previous studies (Aikawa & Fujii, ; Fujii & Aikawa, ). It consisted of seven blocks, and in each block participants were instructed to respond as quickly and correctly as they could.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many implicit concepts in various psychological research fields were revealed using by IAT. For example, there were personality aspect such as stereotype [7] and self-esteem, psychopathological aspect such as anxiety and spider phobia [8,9]. Also with respect to depression, several research investigated relationship between implicit self-esteem and depressed symptom.…”
Section: Depression and Implicit Cognitionmentioning
confidence: 99%